Autograph album of Union soldiers at Libby Prison - Unknown author
Autograph album, 1864-1864, of Union soldiers imprisoned at Libby Prison, Richmond, Virginia, including rank, regiment, and home addresses of the officers. Signatures are compiled in a printed album which also contains 5 engravings and a hand-colored sketch.
Gift of Mrs. Hampton L. Carson.; 1905 acquired
Keywords: Autographs; United States--History--Civil War, 1861-1865--Prisoners and Prisons